Slug Waternet: Inovasi Filtrasi Air Sungai Berbasis Internet Of Things Berdasarkan Biomimikri Nudibranchia Menuju Green Economy 2045 - Syukriyya Zuhrotul Endang Purwaningsih (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
The problem of water pollution in Indonesia is still high, especially from household waste. This research aims to design an innovative river water purification tool using Internet of Things (IoT) technology based on biomimicry of the digestive mechanism of Nudibranchia. This research uses the Research and Development (R & D) method to produce Slug Waternet products and experimental methods for modeling. Data collection techniques are based on library research. The approach used is an engineering design process through the stages of problem and need identification, data and information collection, conceptual design and prototype development. The research results show that this innovation is relevant to green economic principles that support public health to achieve the Golden Generation 2045. The implementation of this tool is expected to overcome limited clean water, improve community welfare, and maintain river ecosystems